Influence of Risk Taking on Business Performance: Examining the Difference between Migrant and Non-Migrant Entrepreneurs - Killa, Maklon Felipus; Danga, Yestiani Yaku (Jurnal Minds: Manajemen Ide dan Inspirasi, 2026)
This study investigates the impact of risk taking on business performance and examines whether this relationship differs between migrant and non-migrant entrepreneurs. Survey data from 101 small and medium enterprise (SME) owners are analyzed using Moderated Regression Analysis (MRA) to test the proposed model. The results indicate that risk taking has a positive effect on business performance. Additionally, migration status moderates this relationship, demonstrating that the effectiveness of risk-taking behavior varies between migrant and non-migrant entrepreneurs. These findings suggest that entrepreneurial performance is influenced by both strategic behavioral orientation and socio-contextual positioning. As the emerging integration of entrepreneurial orientation and migrant entrepreneurship, the study underscores the significance of entrepreneur heterogeneity in explaining SME performance. The results contribute to the risk–taking–performance literature and offer practical implications for the development of differentiated entrepreneurial policies.